Identifying macroeconomic effects of refugee migration to Germany - Enzo Weber; Roland Weigand (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2016)
This study investigates impacts of migration on the German economy, explicitly distinguishing refugee and non-refugee immigration. We propose a macroeconometric modelling approach complemented by instrumental variable techniques. We find that non-refugee immigration has more beneficial medium-run effects on GDP and the labour market. – – Diese Studie untersucht ökonomische Effekte der Immigration nach Deutschland, wobei explizit zwischen der Einwanderung Asylsuchender und sonstiger Einwanderung unterschieden wird. Wir schlagen einen makroökonometrischen Modellansatz mit Verwendung von Instrumentvariablen vor. In der mittleren Frist hat die Immigration Nichtasylsuchender einen günstigeren Effekt auf BIP und Arbeitsmarkt.
Keywords: F22; E24; C32; C36; 330; immigration; economic effects; macroeconometric modelling; instrumental variables